2016
DOI: 10.1016/j.apsb.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Three pairs of alkaloid enantiomers from the root of Isatis indigotica

Abstract: Three pairs of enantiomerically pure alkaloids with diverse structure features, named isatindigoticoic acid A and epiisatindigoticoic acid A [(−)-1 and (+)-1], phaitanthrin A and epiphaitanthrin A [(−)-2 and (+)-2], and isatindopyrromizol A and epiisatindopyrromizol A [(−)-3 and (+)-3], respectively, were isolated from an aqueous extract of the roots of Isatis indigotica. Racemic and scalemic mixtures of these enantiomers were separated by HPLC on a chiral semi-preparative column. Their structures including ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…This consideration would also be valid for some of the other herbal medicines. Additionally, our previous and present results 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 reveal that, in the ban lan gen decoction there are diverse active components against different types of viruses and continuously provide novel candidate for further studies of synthetic/biosynthetic and medicinal chemistry as well as pharmacology.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…This consideration would also be valid for some of the other herbal medicines. Additionally, our previous and present results 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 reveal that, in the ban lan gen decoction there are diverse active components against different types of viruses and continuously provide novel candidate for further studies of synthetic/biosynthetic and medicinal chemistry as well as pharmacology.…”
Section: Discussionsupporting
confidence: 59%
“…Especially differences of the chemical shifts for most of the pairing signals were less than Δ δ C ±0.1. As compared with those of the reported compounds from this plant 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , these spectroscopic data suggested that 1 was an unusual asymmetric dimer of alkaloid containing three sulfur atoms, of which the structure was further elucidated by 2D NMR data analysis.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The extraction procedures also differ from a classic protocol of utilization by decocting the medicines with water. Therefore, as part of our program to systematically study the chemical diversity of traditional Chinese medicines and their biological effects 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , an aqueous decoction of the raw lateral roots of A. carmichaelii was investigated. In previous papers, we reported four new hetisan-type, three new napeline-type, a new arcutine-type, and a novel type C 20 -diterpenoid alkaloids, twenty-six new aconitane-type C 19 -diterpenoid alkaloids including four unique glycosidic neoline derivatives with isomeric arabinosyls, two new 2-(quinonylcarboxamino)benzoates, and seven new aromatic acid derivatives, as well as solvent-/base-/acid-dependent transformation and equilibration between alcohol iminium and aza acetal forms of the napeline-type C 20 -diterpenoid alkaloids 43 , 44 , 45 , 46 , 47 , 48 , 49 .…”
Section: Introductionmentioning
confidence: 99%
“…Indole alkaloids are an important class of organic molecules that contain one or more indole or indoline motifs. They widely distribute as secondary metabolites in bacteria, fungi, plants and animals1., 2., 3.. Some indole alkaloids have been demonstrated to be cytotoxic ( e.g.…”
Section: Introductionmentioning
confidence: 99%